2006
DOI: 10.1002/jsfa.2574
|View full text |Cite
|
Sign up to set email alerts
|

Differential sensitivity of Desi (small‐seeded) and Kabuli (large‐seeded) chickpea genotypes to water stress during seed filling: effects on accumulation of seed reserves and yield

Abstract: Water stress during the reproductive phase, especially during seed development, is considered detrimental for chickpea yield. In the present study, the relative sensitivity of Desi and Kabuli chickpea types to water stress during seed filling was assessed in terms of effects on quantitative and qualitative aspects of seed yield. Leaves of both types experienced stress injury (evaluated as electrolyte leakage) to the same extent and possessed almost similar values of water potential at the end of 14 days of wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 33 publications
6
22
0
Order By: Relevance
“…The albumin fraction in chickpea has been reported to represent 150–250 g kg −1 of the total cotyledonary protein, whereas globulin, a storage protein, constitutes 600–800 g kg −1 of the extractable protein 9. The albumin, globulin, glutelin and prolamin fractions have been found to decrease in stressed seeds of Kabuli and Desi chickpea cultivars 25. Thus the chickpea cultivars used in the present study had similar values to those reported in the literature.…”
Section: Resultssupporting
confidence: 87%
“…The albumin fraction in chickpea has been reported to represent 150–250 g kg −1 of the total cotyledonary protein, whereas globulin, a storage protein, constitutes 600–800 g kg −1 of the extractable protein 9. The albumin, globulin, glutelin and prolamin fractions have been found to decrease in stressed seeds of Kabuli and Desi chickpea cultivars 25. Thus the chickpea cultivars used in the present study had similar values to those reported in the literature.…”
Section: Resultssupporting
confidence: 87%
“…In chickpea, the prolamin fraction represents 28% of the storage protein fraction (Nayyar et al, 2006), which is much lower than that in maize (Azevedo et al, 2003) but considerably higher than the concentrations observed for sorghum, which varied from 2-13% among the genotypes tested in this study. In transgenic soybean lines expressing a maize gamma-zein, the contents of such proteins were considerably higher than that of the untransformed soybean line (Li et al, 2005).…”
Section: Storage Protein Analysismentioning
confidence: 79%
“…The leaf water potential is a prominent character that can be selected for improving drought tolerance of different crops (Nayyar et al, 2006). The leaf water potential was significantly influenced and decreased markedly in the studied varieties due to water stress at booting and anthesis stages (Table 1).…”
Section: Fig 4 Intercepted Par Of Wheat Varieties Under Water Deficmentioning
confidence: 99%